Final answer:
Evaluating the expression p^3 - 94 + 3r + 2 with given values, the result is 136.
Step-by-step explanation:
To evaluate the expression p^3 - 94 + 3r + 2 for p = 6, q = 2, and r = 4, we need to substitute these values into the expression and simplify:
- First, calculate p^3: 6^3 = 6 * 6 * 6 = 216.
- Next, substitute p and r into the expression and add 2: 216 (from step 1) - 94 + (3*4) + 2.
- Multiply 3 by r: 3 * 4 = 12.
- Now, combine all parts of the expression: 216 - 94 + 12 + 2 = 136.
The result of the expression p^3 - 94 + 3r + 2 given the values for p, q, and r is 136.